The use of manner demonstratives in discourse: A contrastive study of Wan (Mande) and Kambaata (Cushitic) - (:unkn) unknown (My University, 2020)
This chapter compares manner demonstratives in two unrelated African languages,Kambaata (Cushitic, Ethiopia) and Wan (Mande, Côte d’Ivoire). Both languages have specialised manner demonstratives, yet differ strikingly in their typological profile and in the way the manner demonstratives behave syntactically. Through systematic comparison of data from both languages, similarities, which are likelydue to common semantic mechanisms of meaning extension, and differences, which are likely due to structural differences between the languages, are identified. It is argued that, despite the shared core meanings, manner demonstratives belong to different syntactic classes in Kambaata and in Wan. The difference in syntactic category helps account for the striking dissimilarities in the range of attested extended uses.
Keywords: African Research